Combined neuronal and inducible nitric oxide synthase inhibition in ovine acute lung injury - Lange, Matthias (2009)
OBJECTIVE: Acute lung injury (ALI) with subsequent pneumonia and sepsis represents a major cause of morbidity and mortality in thermally injured patients. Production of nitric oxide (NO) by the neuronal and inducible NO synthase (nNOS, iNOS) may be critically involved in the pathophysiology of the disease process at different time points and thus specific inhibition at different times may represent an effective treatment regimen. DESIGN: Prospective, controlled, randomized trial. SETTING: University research laboratory. SUBJECTS: Eighteen chronically instrumented, adult, female sheep. INTERVENTIONS: Following baseline measurements, the animals were allocated to either sham-injured, non-treated controls (sham), injured, non-treated controls (control), or injured animals treated with continuous infusion of 7-nitroindazole, a specific nNOS inhibitor, during the first 12 hrs post-injury and infusion of BBS-2, a specific iNOS inhibitor, during the next 12 hrs. Injury was induced by 48 breaths of cotton smoke and subsequent instillation of Ps. aeruginosa into the lungs. All sheep were mechanically ventilated and fluid resuscitated for the entire duration of the 24-hour experiment. MEASUREMENTS AND MAIN RESULTS: The injury induced severe pulmonary dysfunction which was associated with increases in lung edema formation, airway obstruction, and vascular endothelial growth factor (VEGF), 3-nitrotyrosine (3-NT), and poly(ADP ribose) (PAR) expression in lung tissue. The treatment reduced the degree of airway obstruction and improved pulmonary gas exchange, whereas the development of lung edema was not affected. The increases in lung tissue VEGF, 3-NT, and PAR expression were attenuated by the treatment. CONCLUSIONS: The combination of early nNOS and delayed iNOS inhibition shows potential benefit in ovine ALI by reducing nitrosative stress in the lung and limiting the degree of airway obstruction.